The circulation of children : kinship, mobility, and morality in Ayacucho - Leinaweaver, Jessaca B. (Latin America otherwise., 2008)
Analyzes the practice of informal adoption and child circulation between communities in Peru, showing how these historical practices respond to and are constrained by state and international efforts to concretize family and love.